Current Research Trends on Last-Mile Logistics in Latin America during the Period 2003-2022 - Andre Mayer Aguirre, Edgar (2024)
The objective of this research is to determine the impact of current research trends on last-mile logistics in Latin America during the period 2003-2022, because it has become a crucial aspect within the supply chain. To achieve this, three specific objectives were established to delve deeply into the investigation. Regarding the research methodology, a systematic review of scientific literature from the Scopus database was conducted, emphasizing current trends such as e-commerce, environmental awareness, and cost reduction. As for the paper information, trends in last-mile logistics currently observed were taken into account, with a large percentage of publications falling into Q1 (68.4%), Q2 (26.3%), and Q3 (5.3%). The analysis of the articles highlights the evolution of trends in last mile logistics and shows the importance of e-commerce management to increase production and diversify supply. In addition, environmental awareness and its key role in the development of logistics are emphasized.